2015
DOI: 10.1590/2359-3997000000043
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of haemoglobin A1c in a Portuguese adult population

Abstract: Objective: Haemoglobin A1c (Hb A1c) is routinely used for monitoring glycemic control in patients with diabetes. Hb A1c seasonal fluctuations can be directly related to different biological, geographical and cultural influences. Our purpose was to evaluate seasonal variation of Hb A1c in a hospitalbased adult population over a period of 5 years. Materials and methods: We analyzed retrospectively monthly Hb A1c mean values (DCCT, %) based on all the assays performed to adult patients at a tertiary care universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
4
19
1
Order By: Relevance
“…2 These crises should be preventable with education of patients and healthcare professionals (HCPs). However, studies show significantly poor knowledge in both groups, 3,4 leading to failure to increase…”
Section: Poor Knowledge Of Safety Aspects Of Long-term Steroid Use Ammentioning
confidence: 99%
See 3 more Smart Citations
“…2 These crises should be preventable with education of patients and healthcare professionals (HCPs). However, studies show significantly poor knowledge in both groups, 3,4 leading to failure to increase…”
Section: Poor Knowledge Of Safety Aspects Of Long-term Steroid Use Ammentioning
confidence: 99%
“…[1][2][3][4] Potential susceptibilities to seasonal change of HbA1c include inappropriate dietary calorie intake and insufficient physical activity in winter. In our hospital, the majority of diabetes patients are farmers and their physical activity is relatively lower in winter (agricultural off-season) than in summer (busy farming season).…”
Section: Sodium Glucose Co-transporter 2 Inhibitors Successfully Attementioning
confidence: 99%
See 2 more Smart Citations
“…In the treatment of patients with type 2 diabetes mellitus, it is important to lower the blood glucose level and keep the value constant. However, many reports have stated that hemoglobin A1c (HbA1c) levels in patients with type 2 diabetes mellitus fluctuate throughout the year. Surveys in Japanese patients showed that the level generally increased in winter and decreased from summer to autumn.…”
Section: Introductionmentioning
confidence: 99%